Optimalisasi Luberan Sumber Air Melalui Pembangunan Pembangkit Picohydro Menggunakan Axial-Turbine di Desa Ngampungan, Bareng, Jombang - Hidayatul Nurohmah; Machrus Ali; Laudhie Primadonni Kusumajaya; Achmad Afandi (Universitas Darul Ulum, 2026)
Pandansili Tourism Site in Ngampungan Village, Bareng District, Jombang Regency, is a bathing tourism destination developed by the village-owned enterprise and Tourism Awareness Group since 2019. The situational analysis indicates that the partner requires renewable-energy innovation to reduce operational costs, strengthen educational tourism, and improve management capacity. This community service program utilizes spring-water overflow through a picohydro power plant design using an axial turbine. The technical data refer to the ZD760-LM-(18-20) axial-flow turbine-generator with 220 V AC rated voltage, 2 kW rated power, 1-5 m operating head, 0.02-1.0 m3/s water-flow range, and continuous-duty operation. At a nominal head of 3 m with turbine efficiency of 0.65 and generator efficiency of 0.85, the discharge required to produce 2 kW is approximately 0.123 m3/s. The implementation method consists of partner coordination, discharge and head survey, SWOT analysis, intake-turbine-generator-control-panel design, operation-maintenance training, and energy-utilization evaluation. The SWOT analysis shows an IFE score of 5.56 and an EFE score of 5.01, placing Pandansili development in Quadrant I with an aggressive/offensive strategy. The energy output is directed to tourism-area lighting, renewable-energy educational information boards, simple sensor/monitoring loads, and demonstration loads. The program is expected to improve energy independence, add educational tourism value, and strengthen Pokdarwis competence in managing appropriate technology based on local potential.